Social work students' reflection about conducting child welfare assessment in a guided case-based learning environment. - Opio-Göres, Mary; Kollar, Ingo; Dorner, Birgit (Social Work Education, 2026)
To teach about child welfare assessments, social work educators frequently draw on the use of authentic or fictitious cases from social work practice. Such cases provide the opportunity of bridging the theory-practice gap. However, they can be overwhelming given the vast amount of information presented. Additional support is warranted when teaching with cases. In this article, we investigate how students reflect about their learning experience conducting child welfare assessment in a guided case-based learning (GCBL) environment. A qualitative content analysis of written responses of N = 70 social work students from five different universities in Bavaria (Germany) examined implicit and explicit meanings of elements of the learning environment that students paid attention to, what elements they perceived as helpful or hindering, and what factors they attributed difficulty to. Results revealed that the GCBL environment was well received. Features integrated into the GCBL environment helped students to focus on important steps of an assessment. Nonetheless, some students perceived breaking down the exercise into smaller elements as an interference of their problem-solving process. We argue that the potential of GCBL can be improved by paying attention to instruction clarity and by incorporating possibilities of interaction and feedback.